WORLD-RENOWNED PLASTIC SURGEONS LAUD USM POSTGRADUATE PLASTIC SURGERY PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, KELANTAN, 24 May 2015 – The Master of Surgery (Plastic Surgery) Programme offered by the School of Medical Sciences, Universiti Sains Malaysia (USM) is proven to be able to produce plastic surgeons of high calibre, knowledgeable and highlyskilled in the field of plastic and reconstructive surgery.